(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The objective of social marketing is to solve or reduce social problems of any kind, whether related to public health, employment, education, housing, transportation or the environment, among others; that is, any benefit of society as a whole. Similarly, it is widely used by companies to raise awareness about a particular issue, which have the objective of involving people with a cause and without any commercial interest, sensitizing the target audience. Companies are increasingly aware of the importance of the common good, social causes and sustainable actions, it is for this reason that social marketing has been key in the current situation that is experienced worldwide with the pandemic generated by COVID-19, which in many cases has forced them to modify internal strategies aimed at their employees to make them aware of new ways of living and socializing; In addition to that, social distancing has required new methods of working and collaborating remotely. Based on the above, social marketing brings great benefits, not only for companies and consumers, but also for the entire society.